ENHANCEMENT OF SURFACE QUALITY AND TRIBOLOGICAL PROPERTIES USING BALL BURNISHING PROCESS - El-Tayeb, N. S. M.; Low, K. O.; Brevern, P. V. (TAYLOR & FRANCIS INC, 2008)
Surface treatment is an important aspect of all manufacturing processes to impart specific physical, mechanical and tribological properties. Burnishing process is a post-machining operation in which the surface of the workpiece is compressed by the application of a ball or roller to produce a smooth and work-hardened surface by plastic deformation of surface irregularities. In the present study, simple and inexpensive burnishing tools, with interchangeable adapter for ball and roller were designed and fabricated to meet the requirements of the present study. Then, ball burnishing processes were carried out on aluminium 6061 under different parameters and different burnishing orientations to investigate the role of burnishing speed, burnishing force and burnishing tool dimension on the surface qualities and tribological properties. The results showed that burnishing speed of 330rpm and burnishing force of 160N produce optimum results. Meanwhile, a decrease in the burnishing ball diameter leads to a considerable improvement in the surface roughness up to 75%. On the other hand, parallel burnishing orientation exhibits lower friction coefficient compared to cross burnishing orientation. Furthermore, ball burnishing process is capable of improving friction coefficient by 48% reduction and weight loss by 60-80% reduction of burnished surface of Aluminum 6061. These findings are further supplemented by the surface features as seen in SEM photomicrographs.